CRUELTY IN ART AS A SOCIAL PROTEST - Бородіна, Наталія (Ukrainian Cultural Studies, 2023)
Art events are one of the best ways to draw attention to social issues: they are usually vivid and thought-provoking, become a source of long discussions, and ultimately can be a driver of social change. To increase the expressiveness of these actions such provocative methods as shocking cruelty, violence, and violations of moral standards were mostly used. Especially often these methods were used to protest against events related to cruelty and violence – including war. Currently, the war in Ukraine needs maximum publicity, thus to increase the impact on the audience many artists try to reproduce the war crimes of Russia in artistic performances with shocking cruelty similar to the one that took place in the crimes themselves. At the same time, the question arises whether this really attracts attention in favor of Ukraine. The purpose of the article is to discover the phenomenon of cruelty in the art of social protest. Results: The conducted research shows that shocking cruelty as expressive language does not attract attention as effectively as Ukrainians would like. If the viewer was not warned about the scenes of cruelty, then according to the ethical standards of Europe such performances are seen as a violation of the audience's rights and so become condemned. If the informed consent of the viewer has been obtained, then a photo, documentary video, and puppetry have a more convincing effect than acting. Methods that moderate the provocativeness of the performance without shocking brutality allow to achieve better results. Quite peaceful, non-provocative art actions – such as charity concerts and exhibitions, participation in marches, demonstrations, murals in support of Ukraine, painting buildings in Ukrainian colors, petitions to rename streets, etc. – also achieve good results. Conclusions: The study of the phenomenon of cruelty in the art of social protest showed that choosing shockingly violent forms of performance in art actions is based on the desire to punish the "offender", to wish the same brutal revenge, and to show the scale of the problem by its literal reproduction. However, the recipient perceives such performances differently, thus artistic methods need to be adjusted.
Keywords: artistic resistance; performance; art of war; provocative art; cruelty